1993
DOI: 10.1002/j.2162-6057.1993.tb01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Changes in Creativity in the Second Half of life: A Life‐Span Developmental Perspective

Abstract: Research on the relationship between creativity and age has been based on two seemingly incompatible sets of assumptions. The deficit approach maintains and has demonstrated that creative productivity and age have a linear relationship—that is, creativity declines over the life‐span. The alternate approach, upon which the present paper is founded, maintains that creative productivity and creative ability are not identical. Further, this life‐span developmental approach posits that supposed declines in creativi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
13
0
2
Order By: Relevance
“…Our findings are consistent with the two approaches to the study of creativity and aging identified by Sasser-Coen (1993): the deficit approach and the lifespan developmental approach. The deficit approach suggests that creativity declines with age along with other cognitive processes (also see McCrae, 1987& McCrae, Arenberg, & Costa, 1987.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are consistent with the two approaches to the study of creativity and aging identified by Sasser-Coen (1993): the deficit approach and the lifespan developmental approach. The deficit approach suggests that creativity declines with age along with other cognitive processes (also see McCrae, 1987& McCrae, Arenberg, & Costa, 1987.…”
Section: Discussionsupporting
confidence: 89%
“…These studies, showing an age-related decline in productivity, do not necessarily imply a decline due solely or even primarily to age-related changes in cognitive processes (Crozier, 1999;Esquivel & Hodes, 2003;Sasser-Coen, 1993;Simonton, 1990). In fact, few studies have focused on the cognitive processes underlying the creativity of young adults or college students -the typical participants in creativity studies; far fewer studies focus on the cognitive processes underlying creativity in the aged.…”
Section: Introductionmentioning
confidence: 99%
“…As with play, there are many biological and cultural factors that can influence creativity, such as personality, socio-cultural norms, attitudes, choice of profession, and age (Guastello & Shissler, 1994;Sasser-Coen, 1993). Most people experience their creativity in one form or another.…”
Section: Creativity and Its Relationship To Playmentioning
confidence: 97%
“…Similarly, one of the fundamental thinking processes that may affect the development of creativity is the flexibility to tolerate the ambiguity of not having a specific goal (Sasser-Coen, 1993). For some, improved flexibility and adaptability are benefits of creativity (Morgan & Wampler, 2003).…”
Section: Creativity and Its Relationship To Playmentioning
confidence: 99%
See 1 more Smart Citation